THE APPLICATION OF COGNITIVE AND METACOGNITIVE LISTENING TECHNIQUES TO IMPROVE STUDENTS' COMPREHENSION - Kakhorova Mukhabat Askaraliyevna (Bright Mind Publishing, 2025)
The article explores the importance of strategy instruction for high school ELLs, highlights key listening strategies, and outlines practical ways teachers can implement these strategies to enhance second language (L2) listening skills. However, many ELL students struggle with listening due to the complexity of spoken English, unfamiliar accents, and rapid speech.
Keywords: Cognitive and metacognitive benefits, strategy instruction, listening development, language skills.